2020
DOI: 10.1186/s13018-020-02119-1
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular vs. intravenous administration: a meta-analysis of tranexamic acid in primary total knee arthroplasty

Abstract: Background The optimal dosage and administration approach of tranexamic acid (TXA) in primary total knee arthroplasty (TKA) remains controversial. In light of recently published 14 randomized controlled trials (RCTs), the study aims to incorporate the newly found evidence and compare the efficacy and safety of intra-articular (IA) vs. intravenous (IV) application of TXA in primary TKA. Methods PubMed, Embase, Web of Science, and Cochrane Library we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
2
17
0
1
Order By: Relevance
“…Li et al reported that the intravenous tranexamic acid group showed a greater postoperative hemoglobin drop than the IA group. 25 Similarly, in the current study, the mean variation of Hct in the intraarticular group was 4.49 and 6.82 in the intra-venous tranexamic acid group (p = 0.001). In contrast to the above studies, in a review of six randomized controlled and meta-analysis studies in total knee replacements compared results in terms of intraoperative blood losses and number of blood transfusions, the authors did not find any difference between blood transfusions and thromboembolic complications to compare results of intraarticular and intravenous tranexamic acid.…”
Section: Discussionsupporting
confidence: 74%
“…Li et al reported that the intravenous tranexamic acid group showed a greater postoperative hemoglobin drop than the IA group. 25 Similarly, in the current study, the mean variation of Hct in the intraarticular group was 4.49 and 6.82 in the intra-venous tranexamic acid group (p = 0.001). In contrast to the above studies, in a review of six randomized controlled and meta-analysis studies in total knee replacements compared results in terms of intraoperative blood losses and number of blood transfusions, the authors did not find any difference between blood transfusions and thromboembolic complications to compare results of intraarticular and intravenous tranexamic acid.…”
Section: Discussionsupporting
confidence: 74%
“…Li’s research suggested topical usage: topical TXA reduced 33.38 ml more than IV TXA did on total blood loss (WMD 33.38, 95% CI, 19.24–47.51). However, Li et al (2020) demonstrated insignificant differences in the blood transfusion rate and adverse effects. In addition, similar outcomes were found in oral and IV TXA for all aspects.…”
Section: Discussionmentioning
confidence: 88%
“…In terms of dosage, Chen et al suggested that a high dose of IV TXA (30 mg/kg) was more effective than a low dose (15–20 mg/kg) in reducing blood loss without increasing the risk of DVT ( Chen et al, 2014 ). However, the heterogeneity may come from selection biases: Sukeik et al (2020) , Chen et al, and Wu et al (2017) mentioned that patients with a cardiovascular disease history and renal insufficiency were excluded, but Guo et al, Kirsch et al (2017) , and Li et al (2020) did not. As for administration routes, detailed outcomes are displayed in Supplementary Appendix S15 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the most updated systematic review and meta-analysis by Li and colleagues comparing intravenous versus intra-articular TXA in total knee replacement surgery reported greater reduction of intraoperative blood loss and incidence of blood transfusion in those who received intra-articular TXA. 39 Thus, future adequately powered RCTs are warranted to fill knowledge gap with regard to the efficacy and safety of different route of TXA administration in arthroscopic ACLR surgery. Of note, the threshold of blood transfusion varies from one study to another, which may potentially introduce variances to the finding.…”
Section: Discussionmentioning
confidence: 99%